Laminated sheet for forming alloy, method for manufacturing negative electrode for non-aqueous electrolyte battery, and method for manufacturing

By using an alloy forming laminate sheet for forming a carbon layer on the surface of the aluminum foil in advance and stacking it with lithium layers to form a lithium-aluminum alloy layer, the problems of complex and low efficiency of the negative electrode manufacturing process of nonaqueous electrolyte batteries are solved, and the effects of excellent low-temperature load characteristics and high productivity are achieved.

CN119923726APending Publication Date: 2025-05-02MAXELL LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380067904.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, when manufacturing the negative electrode of a nonaqueous electrolyte battery, the process of coating the composition is complicated and inefficient, especially in small-area electrodes, and the manufacturing of large-area electrodes takes a long time to affect productivity.

Method used

A laminated sheet for alloy formation in which a carbon layer is formed on the surface of the aluminum foil is used in advance, and stacked with lithium layers to form a lithium-aluminum alloy layer, thereby simplifying the manufacturing process of the negative electrode and improving production efficiency.

Benefits of technology

The negative electrode produced by this method exhibits excellent load characteristics at low temperatures and has a significant increase in productivity, avoiding deviations and waste of time during the coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923726A_ABST
    Figure CN119923726A_ABST
Patent Text Reader

Abstract

Provided are: an alloy-forming laminated sheet for producing a negative electrode capable of constituting a non-aqueous electrolyte battery having excellent load characteristics at low temperatures; a method for producing a negative electrode and a non-aqueous electrolyte battery with good productivity; and a method for producing a non-aqueous electrolyte battery. This method for producing a negative electrode for a non-aqueous electrolyte battery is a method for producing a negative electrode having a negative electrode active material layer having a lithium layer and a lithium-aluminum alloy layer formed on the surface of the lithium layer, and a carbon layer formed on the surface of the negative electrode active material layer, the production method is characterized by comprising: a step for laminating an alloy-forming laminated sheet and a lithium layer such that the surface of the aluminum foil on the opposite side from the carbon layer is in contact with the lithium layer, the alloy-forming laminated sheet having an aluminum foil and a carbon layer formed on one surface thereof as a separate sheet; and a step for forming the negative electrode active material layer by reacting lithium in the lithium layer with aluminum in the aluminum foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an alloy-forming laminated sheet for manufacturing a negative electrode of a nonaqueous electrolyte battery having excellent load characteristics at low temperatures and a method for manufacturing a negative electrode for a nonaqueous electrolyte battery using the alloy-forming laminated sheet. In addition, the present invention relates to a method for manufacturing a nonaqueous electrolyte battery using the negative electrode manufacturing method to manufacture a negative electrode. Background Art

[0002] Non-aqueous electrolyte batteries such as lithium primary batteries and lithium secondary batteries having a lithium-aluminum alloy in a negative electrode are widely used in various applications, and attempts to improve their characteristics are also being made.

[0003] For example, the following technology is proposed in Patent Document 1: by using a negative electrode having a lithium layer with a lithium-aluminum alloy layer formed on the surface and further having a carbon layer on the above-mentioned lithium-aluminum alloy layer, the high-temperature storage characteristics and low-temperature load characteristics of a non-aqueous electrolyte battery (non-aqueous electrolyte battery) are improved.

[0004] Patent Document 2 describes a current collector for an electrochemical device in which a conductive film containing a carbon material is formed on one or both surfaces of an aluminum foil.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2020 / 250816

[0008] Patent Document 2: International Publication No. 2012 / 108212 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, when manufacturing the negative electrode, when using the method described in Patent Document 1 of laminating an aluminum layer (aluminum foil) on the surface of the lithium layer and then applying a composition obtained by dispersing carbon particles in an organic solvent on the surface of the aluminum layer to form a carbon layer, the battery must be assembled through a process of applying the composition on an aluminum foil with a limited area. Therefore, in the case of a small electrode area such as a coin-shaped battery, the amount of the composition applied is prone to deviation. In addition, even in the case of a cylindrical battery or other electrode having a large area to a certain extent, since the composition is applied one by one on the cut aluminum foil and dried, time is required in the manufacturing process of the negative electrode, and there is room for improvement in the productivity of the negative electrode and the battery.

[0011] The present invention has been completed in view of the above situation, and its purpose is to provide an alloy-forming laminate sheet for producing a negative electrode of a non-aqueous electrolyte battery that is capable of constituting an excellent load characteristic at low temperatures, and further to provide a method for producing a negative electrode for a non-aqueous electrolyte battery and a method for producing a non-aqueous electrolyte battery by using the above-mentioned alloy-forming laminate sheet with good productivity.

[0012] Methods for solving problems

[0013] The alloy forming laminated sheet of the present invention is an independent sheet consisting of an aluminum foil (including an aluminum foil containing only Al (and inevitable impurities) and an aluminum alloy foil containing an alloy of Al and other elements. Unless otherwise specified, the "aluminum foil" described in this specification shall apply the same below) and a carbon layer formed on a single side of the above-mentioned aluminum foil, and is used to make the surface of the above-mentioned aluminum foil opposite to the carbon layer contact with the lithium layer to form a lithium-aluminum alloy layer on the surface of the above-mentioned lithium layer.

[0014] In addition, the manufacturing method of the negative electrode for a non-aqueous electrolyte battery of the present invention (hereinafter sometimes referred to as the "negative electrode") is a method for manufacturing a negative electrode having a negative electrode active material layer and a carbon layer, wherein the negative electrode active material layer has a lithium layer and a lithium-aluminum alloy layer formed on the surface of the lithium layer, and the carbon layer is formed on the surface of the negative electrode active material layer. The manufacturing method is characterized in that it comprises a step of stacking the alloy forming laminate sheet and the lithium layer in such a manner that the surface of the aluminum foil of the alloy forming laminate sheet of the present invention opposite to the carbon layer contacts the lithium layer, and a step of reacting the lithium in the lithium layer with the aluminum of the aluminum foil to form the negative electrode active material layer.

[0015] In addition, the manufacturing method of the non-aqueous electrolyte battery of the present invention is a method for manufacturing a non-aqueous electrolyte battery having a positive electrode, a negative electrode and a separation layer between the above-mentioned positive electrode and the above-mentioned negative electrode, characterized in that the above-mentioned negative electrode has a negative electrode active material layer and a carbon layer, the above-mentioned negative electrode active material layer has a lithium layer and a lithium-aluminum alloy layer formed on the surface of the above-mentioned lithium layer, the above-mentioned carbon layer is formed on the surface of the above-mentioned negative electrode active material layer, and the above-mentioned negative electrode is formed by the above-mentioned method for manufacturing a negative electrode for a non-aqueous electrolyte battery of the present invention.

[0016] Effects of the Invention

[0017] According to the present invention, an alloy-forming laminated sheet for making a negative electrode of a nonaqueous electrolyte battery having excellent load characteristics at low temperatures can be provided. In addition, by assembling a negative electrode and then assembling a battery using the alloy-forming laminated sheet of the present invention, a negative electrode of a nonaqueous electrolyte battery having excellent load characteristics at low temperatures and a nonaqueous electrolyte battery having the negative electrode can be manufactured with good productivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a cross-sectional view schematically showing an example of the nonaqueous electrolyte battery of the present invention. DETAILED DESCRIPTION

[0019] The non-aqueous electrolyte battery manufactured by the manufacturing method of the present invention has a negative electrode, the negative electrode has a negative electrode active material layer and a carbon layer, the negative electrode active material layer has a lithium layer and a lithium-aluminum alloy layer formed on the surface of the lithium layer, and the carbon layer is formed on the surface of the negative electrode active material layer. By having the above-mentioned negative electrode, the reactivity of the negative electrode is improved, and better current collection can be ensured, so the load characteristics of the non-aqueous electrolyte battery at low temperatures (for example, the load characteristics at low temperatures of -30 to -40°C) can be improved.

[0020] The lithium-aluminum alloy layer possessed by the negative electrode can be formed, for example, as follows: an aluminum layer composed of aluminum foil is overlapped with the surface of a lithium layer composed of lithium foil or lithium alloy foil to form a stack, and a carbon layer is formed on the surface of the aluminum layer in the stack (the surface on the opposite side of the lithium layer), and the lithium layer and the aluminum layer are reacted by bringing the formed negative electrode stack into contact with a non-aqueous electrolyte.

[0021] However, when forming a carbon layer on the surface of an aluminum foil cut to the size of a lithium layer in order to form a negative electrode laminate, if a method is adopted in which a composition obtained by dispersing carbon particles in an organic solvent is applied to the aluminum foil cut to form the negative electrode, the surface area of ​​the aluminum foil is limited, so it is difficult to apply the composition uniformly in a short time. For example, in the case of a small electrode area such as a coin-shaped battery, the amount of the composition applied is likely to vary, and the composition is likely to overflow from the aluminum foil during application. On the other hand, even in the case of a cylindrical battery where the electrode area is large to a certain extent, since the composition is applied to the cut aluminum foil one by one and dried, the production of the negative electrode takes time, which is a major cause of the deterioration of the productivity of the negative electrode and the non-aqueous electrolyte battery.

[0022] Therefore, in the manufacturing method of the negative electrode for nonaqueous electrolyte battery of the present invention and the manufacturing method of the nonaqueous electrolyte battery of the present invention, an aluminum foil having a carbon layer formed on the surface in advance is used, and the lithium-aluminum alloy layer of the negative electrode is formed through the process of laminating the aluminum foil with the lithium layer. Thus, for example, after the carbon layer is formed on the surface of the aluminum foil with a large area, the aluminum foil is cut into a required size and provided for the manufacture of the negative electrode, so that the aluminum foil with a uniform carbon layer can be easily obtained in a short time, and the reduction of the productivity of the negative electrode and the nonaqueous electrolyte battery accompanying the formation of the carbon layer can be suppressed.

[0023] Aluminum foil is thin and weak, so it has a surface that is difficult to cut or handle when it is alone. However, by forming a carbon layer on the surface in advance, it is expected that problems in cutting and handling the aluminum foil can be reduced.

[0024] From the above, it can be seen that the non-aqueous electrolyte battery using a negative electrode manufactured by the manufacturing method of the non-aqueous electrolyte battery negative electrode of the present invention and the non-aqueous electrolyte battery manufactured by the manufacturing method of the non-aqueous electrolyte battery of the present invention can more easily and effectively exert the effect brought about by the formation of the carbon layer, and the load characteristics at low temperatures are better.

[0025] <Method for producing negative electrode for non-aqueous electrolyte battery>

[0026] In the manufacturing method of the negative electrode of the present invention, a negative electrode formed by stacking a negative electrode active material layer and a carbon layer on its surface is manufactured through the process of forming a negative electrode stack and the process of forming a negative electrode active material layer; in the process of forming the negative electrode stack, the alloy forming stack and the lithium layer are stacked in such a way that the surface of the aluminum foil opposite to the carbon layer of an independent sheet (alloy forming stack) composed of aluminum foil and a carbon layer formed on a single side of the aluminum foil contacts the lithium layer, thereby forming a negative electrode stack; in the process of forming the negative electrode active material layer, the lithium of the lithium layer of the negative electrode stack reacts with the aluminum of the aluminum foil to form a negative electrode active material layer having a lithium layer and a lithium-aluminum alloy layer formed on its surface.

[0027] As lithium foil or lithium alloy foil for forming a lithium layer, there can be cited foil (lithium foil) composed of Li (and inevitable impurities), foil (lithium alloy foil) composed of Li alloy, etc., in which the Li alloy contains Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, Mo, etc. as alloy components in an amount of less than 40 mass%, preferably less than 10 mass%, and more preferably less than 5 mass%, with the balance being Li and inevitable impurities.

[0028] The thickness of the lithium foil or lithium alloy foil constituting the lithium layer is preferably 0.1 to 1.5 mm.

[0029] The aluminum foil constituting the alloy-forming laminate sheet and used to form the lithium-aluminum alloy layer of the negative electrode can use a foil composed of Al (and inevitable impurities), a foil composed of an Al alloy (aluminum alloy foil), etc., in which the Al alloy contains Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, Mo, etc. as alloy components, and the balance is Al and inevitable impurities (the content of the above alloy components is, for example, a total of less than 50 mass%, preferably less than 10 mass%, and more preferably less than 5 mass%).

[0030] From the viewpoint of more effectively ensuring the effect of forming the lithium-aluminum alloy layer, the thickness of the aluminum foil for forming the lithium-aluminum alloy layer is preferably 1 μm or more, more preferably 3 μm or more, and particularly preferably 5 μm or more.

[0031] On the other hand, when the ratio of the lithium-aluminum alloy layer to the lithium layer is too much, it will lead to a decrease in the negative electrode capacity. In addition, due to the volume expansion of the aluminum foil and the lithium alloy, cracks will occur in the aluminum foil (lithium-aluminum alloy layer), but if the aluminum foil becomes thicker, the above-mentioned cracks will occur deep inside the negative electrode, and when subjected to large vibrations, a part of the lithium-aluminum alloy layer may fall off. Therefore, in a manner such that the thickness of the lithium-aluminum alloy layer formed becomes below a certain value, the thickness of the aluminum foil is preferably set to less than 20 μm, and more preferably set to less than 15 μm.

[0032] As described above, a carbon layer is formed on the surface (single side) of the aluminum foil and used as a laminated sheet for alloy formation. The carbon layer may be composed only of carbon (its particles), but the carbon layer is easily retained on the negative electrode surface, so a binder may be contained together with the carbon. In addition, in the case where the nonaqueous electrolyte battery is a fully solid battery having a solid electrolyte layer, in order to impart ion conductivity, the carbon layer preferably contains a solid electrolyte described later.

[0033] Examples of carbon constituting the carbon layer include carbon black such as furnace black, channel black, acetylene black, and thermal black; graphites such as natural graphite (flake graphite, etc.) and artificial graphite; and fibrous carbon such as vapor-grown carbon fibers and carbon nanotubes. Only one type of these may be used, or two or more types may be used in combination.

[0034] In addition, as binders that can be used for the carbon layer, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyethylene oxide (PEO), acrylic resin, polyacrylic acid, polyvinyl pyrrolidone, etc. In particular, compounds having a 5-membered ring lactam structure such as polyvinyl pyrrolidone can well disperse tiny carbon materials such as carbon black in a state dissolved in a solvent, and are therefore preferably used.

[0035] The content of the binder in the carbon layer is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.5% by mass or less.

[0036] From the viewpoint of satisfactorily ensuring the above-mentioned effect brought about by the formation of the carbon layer, the mass per unit area (weight per unit area) of the carbon layer in the negative electrode is preferably 0.15 mg / cm 2 More preferably 0.3 mg / cm 2 More than 0.5 mg / cm 2However, even if the carbon layer is thickened, the effect will be saturated. In addition, since the negative electrode as a whole becomes thicker, for example, the amount of positive electrode active material that can be introduced into the battery decreases, which may also cause the battery capacity to decrease. Therefore, from the perspective of increasing the battery capacity, the unit area weight of the carbon layer in the negative electrode is preferably 3 mg / cm 2 Below, more preferably 1.5 mg / cm 2 Below, particularly preferably 1.0 mg / cm 2 the following.

[0037] Therefore, in the alloy-forming laminate sheet used in manufacturing the negative electrode, it is preferable to use a laminate sheet having a carbon layer formed on the surface of the aluminum foil within the above-mentioned range of unit area weight so that the unit area weight of the manufactured negative electrode satisfies the above-mentioned value.

[0038] The carbon layer can be formed, for example, by applying a carbon layer-forming composition (liquid composition such as paste or slurry) prepared by dispersing carbon and a binder added as needed in an organic solvent (the binder may be dissolved) on the surface of the aluminum foil and drying the composition.

[0039] As an organic solvent used in the composition for forming the carbon layer, for example, a solvent commonly used in a non-aqueous electrolyte suitable for a battery is preferably used. As specific examples thereof, cyclic carbonates such as ethylene carbonate, propylene carbonate (PC), butylene carbonate, and vinylene carbonate can be cited; chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; ethers such as 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (diethylene glycol dimethyl ether), triethylene glycol dimethyl ether (triethylene glycol dimethyl ether), tetraethylene glycol dimethyl ether (tetraethylene glycol dimethyl ether), methoxyethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran; cyclic esters such as γ-butyrolactone; nitrile, etc., one or more of them can be used, but carbonates such as propylene carbonate may react with lithium to form lithium carbonate, thereby reducing the reactivity of the negative electrode surface. Therefore, from the viewpoint of making it easier to exert the effect of the present invention, it is preferred to use a solvent other than a carbonate, more preferably an ether, and further preferably DME.

[0040] In addition, as the organic solvent used in the carbon layer forming composition, the solvent used when forming a coating such as a slurry having a positive electrode active material can also be used. In the case of using a tiny carbon material such as carbon black, a compound having a five-membered ring lactam structure such as 2-pyrrolidone and N-methyl-2-pyrrolidone (NMP) is preferably used because it can disperse the above carbon material well. The above compound having a five-membered ring lactam structure can also be mixed with the above organic solvent for use.

[0041] As the alloy-forming laminate sheet, a commercially available carbon-coated aluminum foil (such as "SHX (trade name)" manufactured by Shohoku Laminate Industry Co., Ltd.) may be used.

[0042] A negative electrode laminate having a lithium layer and an aluminum foil having a carbon layer on its surface can be formed, for example, by stacking and pressing lithium foil or lithium alloy foil used to constitute the lithium layer and an alloy forming laminate sheet in a manner such that the surface of the aluminum foil of the alloy forming laminate sheet opposite to the carbon layer is in contact.

[0043] The negative electrode can be stacked with a lithium-aluminum alloy layer and a carbon layer on one or both sides of the lithium layer in accordance with the form of the battery. For example, in a battery in which a positive electrode is configured on both sides of the lithium layer of the negative electrode with a separator (diaphragm, solid electrolyte layer) separated, a negative electrode can be used in which a negative electrode active material layer is formed in the form of a lithium-aluminum alloy layer formed on both sides of the lithium layer, and then a carbon layer is stacked on both sides of the negative electrode active material layer. Therefore, when manufacturing a negative electrode in which a lithium-aluminum alloy layer and a carbon layer are stacked on both sides of the lithium layer, a negative electrode stack is used in which an alloy-forming stack is stacked on both sides of a lithium foil or a lithium alloy foil used to constitute a lithium layer. Alternatively, a negative electrode stack can be made by stacking an alloy-forming stack on one side of a lithium foil or a lithium alloy foil used to constitute a lithium layer, and then bending it so that the negative electrode is configured on both sides of the positive electrode to form the same battery as described above.

[0044] The negative electrode may be composed only of a negative electrode active material layer and a carbon layer, wherein the negative electrode active material layer is composed of a lithium layer and a lithium-aluminum alloy layer formed on the surface thereof, but may further include a current collector as necessary.

[0045] As the negative electrode current collector, materials that do not react with lithium, such as copper, nickel, iron, and stainless steel, can be cited as raw materials, and as its form, plain wire mesh, expanded metal mesh, lath mesh, punched metal, metal foam, foil (plate), etc. can be exemplified. The thickness of the current collector is preferably 5 to 100 μm, for example. It is also preferred that a paste-like conductive material such as carbon paste or silver paste is pre-coated on the surface of such a current collector.

[0046] The negative electrode current collector may be preliminarily contacted with one surface of the lithium layer (lithium foil) to form an integrated body, or the lithium foil may be stacked on the negative electrode current collector, and then the alloy forming laminated sheet may be stacked thereon. In addition, after the alloy forming laminated sheet is stacked on the lithium foil, the negative electrode current collector may be arranged on the surface of the lithium foil opposite to the alloy forming laminated sheet.

[0047] The negative electrode active material layer is prepared by reacting the lithium of the lithium layer in the negative electrode stack with the aluminum of the aluminum foil to form a lithium-aluminum alloy layer on the surface of the lithium layer. This process can be implemented before battery assembly. In this case, the negative electrode obtained by changing the aluminum layer of the negative electrode stack to a lithium-aluminum alloy layer is used for the assembly of a non-aqueous electrolyte battery. For example, in the case of manufacturing a non-aqueous electrolyte battery in which a solid electrolyte layer is interposed between the positive electrode and the negative electrode, a negative electrode with a lithium-aluminum alloy layer formed in advance is used.

[0048] When the lithium-aluminum alloy layer is formed in the negative electrode stack before assembling the battery, for example, a method of immersing the negative electrode stack in a non-aqueous electrolyte or its solvent that can be used in the non-aqueous electrolyte battery described later, a method of wetting the surface of the negative electrode stack with the above-mentioned non-aqueous electrolyte or its solvent, etc. can be adopted.

[0049] On the other hand, the negative electrode laminate can also be used to assemble the battery instead of the negative electrode, and the negative electrode laminate is contacted with the nonaqueous electrolyte during its assembly (during the injection of the nonaqueous electrolyte), and a lithium-aluminum alloy layer is formed in the same manner as above to obtain the negative electrode. In the case of manufacturing a nonaqueous electrolyte battery using a nonaqueous electrolyte, the manufacturing process of the negative electrode before the battery assembly can be simplified by the above method, so it is preferred in terms of being able to further improve the productivity of the nonaqueous electrolyte battery.

[0050] In the negative electrode, the lithium-aluminum alloy layer may be formed on the entire surface of the lithium layer, or may be formed only on a portion of the surface of the lithium layer. However, the greater the proportion of the area where the lithium-aluminum alloy layer is formed, the easier it is to ensure the effect brought about by the formation of the lithium-aluminum alloy layer, so the proportion of the area where the lithium-aluminum alloy layer is formed on the surface of the lithium layer is preferably 40% or more, more preferably 70% or more, particularly preferably 90% or more, and most preferably 100%, that is, the lithium-aluminum alloy layer is formed on the entire surface of the lithium layer.

[0051] In the negative electrode after manufacture, the carbon layer is directly arranged on the surface of the negative electrode active material layer, and is essentially stacked on the surface of the lithium-aluminum alloy layer formed. It should be noted that the carbon layer can be formed on the entire surface of the lithium-aluminum alloy layer, or the carbon layer can be formed on a part of the surface of the lithium-aluminum alloy layer. That is, as a laminated sheet for alloy formation, a laminated sheet in which a part of the surface of the aluminum foil is not covered by the carbon layer can be used, and a part of the lithium-aluminum alloy layer formed can also be exposed on the surface of the negative electrode without being covered by the carbon layer. For example, when the lithium-aluminum alloy layer is formed, its surface becomes concave and convex, and the convex part is exposed on the surface of the negative electrode. In addition, the carbon layer can also be scattered in an island shape.

[0052] However, the greater the ratio of the area of ​​the portion where the lithium-aluminum alloy layer and the carbon layer are formed on the lithium layer, the easier it is to ensure the effect of the present invention, so the ratio of the area where the carbon layer is formed on the surface of the lithium-aluminum alloy layer is preferably 40% or more, more preferably 70% or more, particularly preferably 90% or more, and particularly preferably 100%, that is, the carbon layer is formed on the entire surface of the lithium-aluminum alloy layer. Therefore, it is preferred to form a carbon layer on the surface of the aluminum foil of the alloy forming laminated sheet in a manner that the area ratio satisfies the above value.

[0053] Furthermore, in the manufactured negative electrode, it is most preferred that the lithium-aluminum alloy layer is formed on the entire surface of the lithium layer, and the carbon layer is formed on the entire surface of the lithium-aluminum alloy layer.

[0054] <Method for Manufacturing Non-Aqueous Electrolyte Battery>

[0055] The method for manufacturing a nonaqueous electrolyte battery of the present invention forms a negative electrode by the method for manufacturing a negative electrode for a nonaqueous electrolyte battery of the present invention when manufacturing a nonaqueous electrolyte battery having a positive electrode, a negative electrode, and a separator or a solid electrolyte layer between the positive electrode and the negative electrode. That is, the method comprises the following steps: the negative electrode having a negative electrode active material layer and a carbon layer formed on the surface of the negative electrode active material layer is manufactured through a step of forming a negative electrode laminate and a step of forming a negative electrode active material layer; in the step of forming a negative electrode laminate, the alloy forming laminate is laminated with the lithium layer in such a manner that the surface of the aluminum foil opposite to the carbon layer in the alloy forming laminate composed of an aluminum foil and a carbon layer formed on one side of the aluminum foil contacts the lithium layer, thereby forming a negative electrode laminate; in the step of forming a negative electrode active material layer, the lithium-aluminum alloy layer is formed on the surface of the lithium layer by reacting the lithium of the lithium layer of the negative electrode laminate with the aluminum of the aluminum foil, thereby forming a negative electrode active material layer.

[0056] The non-aqueous electrolyte batteries manufactured by the manufacturing method of the present invention include primary batteries and secondary batteries, and also include batteries having a solid electrolyte layer between the positive electrode and the negative electrode (all-solid-state batteries) and batteries having a separator between the positive electrode and the negative electrode and an electrolyte containing a solvent (non-aqueous electrolyte, aqueous electrolyte, and gel electrolyte formed by gelling these electrolytes) (batteries other than all-solid-state batteries), etc.

[0057] In the positive electrode of a non-aqueous electrolyte battery, for example, a mixture containing a positive electrode active material, a conductive aid, a binder, etc. (positive electrode mixture) is formed into a granular shape, or a positive electrode having a structure in which a layer (positive electrode mixture layer) formed by the above-mentioned positive electrode mixture is provided on one side or both sides of a collector.

[0058] As the positive electrode active material, manganese dioxide, lithium-containing manganese oxide (for example, LiMn3O6, a composite oxide having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed, etc.) and a Li content of 3.5 mass % or less, preferably 2 mass % or less, more preferably 1.5 mass % or less, and particularly preferably 1 mass % or less), Li a Ti 5 / 3 O4 (4 / 3≤a<7 / 3) and other lithium-containing composite oxides, vanadium oxides, niobium oxides, titanium oxides, sulfides such as iron disulfide, graphite fluoride, etc.

[0059] Examples of the conductive aid of the positive electrode mixture include flake graphite, acetylene black, Ketjen black, and carbon black. These may be used alone or in combination of two or more.

[0060] Furthermore, examples of the binder of the positive electrode mixture include fluororesins such as PVDF, PTFE, and hexafluoropropylene polymers, and these may be used alone or in combination of two or more.

[0061] When the nonaqueous electrolyte battery is an all-solid battery having a solid electrolyte layer, the positive electrode mixture preferably contains a solid electrolyte.

[0062] The solid electrolyte contained in the positive electrode mixture is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.

[0063] As sulfide-based solid electrolytes, particles such as Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3 glass can be cited. In addition, thio-LISICON-type solid electrolytes (Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3 glass particles can also be used, which have attracted much attention in recent years as materials with high Li ion conductivity. 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Wait 12-12a-b+c+6d- e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 5 12-e X e (Among them, M1 is Si, Ge or Sn, M 2 is P or V, M 3 is Al, Ga, Y or Sb, M 4 is Zn, Ca or Ba, M 5 is S, or S and O, X is F, Cl, Br or I, 0 ≤ a < 3, 0 ≤ b + c + d ≤ 3, 0 ≤ e ≤ 3), a substance having a thiogermanate-type crystal structure.

[0064] As a hydride-based solid electrolyte, for example, LiBH4, a solid solution of LiBH4 and the following alkali metal compound (for example, a solid solution with a molar ratio of LiBH4 to the alkali metal compound of 1:1 to 20:1), etc. can be cited. As the alkali metal compound in the above solid solution, at least one selected from lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide can be cited.

[0065] As a halide-based solid electrolyte, for example, monoclinic LiAlCl4, defect spinel-type or layered LiInBr4, monoclinic Li 6-3m Y m X6 (where 0 < m < 2 and X = Cl or Br), etc. In addition, for example, known substances described in International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can also be used.

[0066] As an oxide-based solid electrolyte, for example, garnet-type Li7La3Zr2O 12 、NASICON-type Li 1+ O Al 1+O Ti 2-O (PO4)3, Li 1+p Al 1+p Ge 2-p (PO4)3, perovskite-type Li 3q La 2 / 3-q TiO3, etc.

[0067] Among these solid electrolytes, from the aspect of high lithium ion conductivity, sulfide-based solid electrolytes are preferred, sulfide-based solid electrolytes containing Li and P are more preferred, and sulfide-based solid electrolytes having a thiogermanate-type crystal structure are further preferred from the aspects of higher lithium ion conductivity and high chemical stability.

[0068] As the sulfide-based solid electrolyte having an argyrodite-type crystal structure, for example, Li6PS5Cl, a sulfide-based solid electrolyte represented by the following general composition formula (1) or the following general composition formula (2), etc. are particularly preferred.

[0069] Li 7-x+y PS 6-x Cl x+y (1)

[0070] In the above general composition formula (1), 0.05≤y≤0.9, -3.0x+1.8≤y≤-3.0x+5.7.

[0071] Li 7-a PS 6-a Cl b Br c (2)

[0072] In the above general composition formula (2), a=b+c, 0 <a≤1.8,0.1≤b / c≤10.0。

[0073] From the viewpoint of reducing grain boundary resistance, the average particle size of the solid electrolyte is preferably 0.1 μm or more, more preferably 0.2 μm or more. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably 10 μm or less, more preferably 5 μm or less.

[0074] When the positive electrode is a molded body of a positive electrode mixture, it can be produced by, for example, mixing a positive electrode active material with a conductive aid, a binder, a solid electrolyte, etc. to prepare a positive electrode mixture, and press-molding the positive electrode mixture into a predetermined shape.

[0075] In addition, in the case of a positive electrode having a positive electrode mixture layer and a current collector, it can be manufactured, for example, through the following steps: the positive electrode active material and the conductive aid as well as the binder, the solid electrolyte, etc. are dispersed in a solvent, a composition (slurry, paste, etc.) containing the positive electrode mixture is prepared (the binder can be dissolved in the solvent), it is applied to the collector and dried, and a pressing treatment such as calendering is performed as needed.

[0076] The solvent of the composition containing the positive electrode mixture can use organic solvents such as water and N-methyl-2-pyrrolidone (NMP). It should be noted that the solvent when the composition containing the positive electrode mixture also contains a solid electrolyte is preferably selected to be difficult to deteriorate the solid electrolyte. In particular, since sulfide-based solid electrolytes, hydride-based solid electrolytes, etc. will cause chemical reactions due to a small amount of water, it is preferred to use non-polar aprotic solvents represented by hydrocarbon solvents such as hexane, heptane, octane, nonane, decane, decalin, toluene, and xylene. In particular, it is more preferred to use a super dehydrated solvent with a water content of 0.001 mass% (10ppm) or less. In addition, fluorine-based solvents such as "Vertrel (registered trademark)" made by Mitsui DuPont Fluorochemicals, "ZEORORA (registered trademark)" made by Japan Zeon Co., Ltd., and "Novec (registered trademark)" made by Sumitomo 3M Co., Ltd., and non-aqueous organic solvents such as dichloromethane and diethyl ether can also be used.

[0077] However, the positive electrode is not limited to the positive electrode produced by the above-mentioned methods, and may be produced by other methods.

[0078] As the composition of the positive electrode mixture of the positive electrode, the amount of the positive electrode active material is preferably 80 to 90% by mass, the content of the conductive aid is preferably 1.5 to 10% by mass, and the content of the binder is preferably 0.3 to 10% by mass. It should be noted that, in the case where the positive electrode mixture contains a sulfide-based solid electrolyte, even if the positive electrode mixture does not contain a binder, the positive electrode mixture may not contain a binder (the content of the binder in the positive electrode mixture is 0% by mass) in order to ensure good moldability.

[0079] In addition, when the positive electrode mixture contains a solid electrolyte, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, preferably 65 parts by mass or less, more preferably 60 parts by mass or less.

[0080] When the positive electrode mixture is a molded body, its thickness is preferably 0.15 to 4 mm. On the other hand, in the case of a positive electrode having a positive electrode mixture layer and a current collector, for example, a positive electrode having a coating layer of a positive electrode mixture formed on a current collector, the thickness of the positive electrode mixture layer (the thickness of each side of the current collector) is preferably 30 to 300 μm.

[0081] When a current collector is used in the positive electrode, as the current collector, for example, a current collector made of stainless steel such as SUS316, SUS430, SUS444, etc. can be cited, and as its form, a plain wire mesh, an expanded metal mesh, a lath mesh, a punched metal, a metal foam, a foil (plate), etc. can be exemplified. The thickness of the current collector is preferably 0.05 to 0.2 mm, for example. It is also preferred that a paste-like conductive material such as carbon paste or silver paste is pre-coated on the surface of such a current collector.

[0082] In the case where the non-aqueous electrolyte battery is an all-solid-state battery, a solid electrolyte layer is used as a separator between the positive electrode and the negative electrode. The solid electrolyte in the solid electrolyte layer can use one or more of the various sulfide solid electrolytes, hydride solid electrolytes, halide solid electrolytes, and oxide solid electrolytes previously exemplified as solid electrolytes that can be used in the positive electrode. However, in order to make the battery characteristics more excellent, it is preferred to contain a sulfide solid electrolyte, and more preferably contain a sulfide solid electrolyte of argyrodite type. Moreover, it is further preferred to contain a sulfide solid electrolyte in both the positive electrode and the solid electrolyte layer, and it is particularly preferred to contain a sulfide solid electrolyte of argyrodite type.

[0083] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.

[0084] The solid electrolyte layer can be formed by the following methods: a method of compressing the solid electrolyte by pressure molding, etc.; a method of applying a solid electrolyte layer-forming composition prepared by dispersing a solid electrolyte in a solvent to a substrate (including a porous body serving as a support), a positive electrode, and a negative electrode and drying the composition, and performing pressure molding such as pressing as needed, etc.

[0085] The solvent used in the solid electrolyte layer-forming composition is preferably a solvent that does not easily degrade the solid electrolyte, and preferably the same solvents as those exemplified above as the solvent for the positive electrode mixture-containing composition.

[0086] The thickness of the solid electrolyte layer is preferably 10 to 500 μm.

[0087] In the case where the non-aqueous electrolyte battery is a battery other than an all-solid-state battery, a separator that becomes a separator between the positive electrode and the negative electrode uses a non-woven fabric or a microporous membrane (microporous membrane). As its raw material, in addition to being able to use polyolefins such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers, in the case where heat resistance is required in relation to the battery use, fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymers (PFA), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), polybutylene terephthalate (PBT), polymethylpentene, polyamide, polyimide, aramid, cellulose, etc. can also be used. The raw materials of the non-woven fabric and the microporous membrane can use only one of the raw materials exemplified above, or two or more. In addition, the nonwoven fabric or microporous membrane that serves as the separator may have a laminated structure in which a plurality of nonwoven fabrics or microporous membranes made of different raw materials are laminated, in addition to the single-layer nonwoven fabric or microporous membrane made of the raw materials exemplified above.

[0088] From the viewpoint of suppressing the reduction of the energy density of the battery, the thickness of the separator is, for example, 500 μm or less, preferably 450 μm or less, and more preferably 300 μm or less. However, if the separator is too thin, the function of preventing short circuit may be reduced. Therefore, in the case of using a non-woven fabric, the thickness is, for example, 30 μm or more, preferably 100 μm or more, and more preferably 150 μm or more. In addition, in the case of using a microporous membrane, it is preferably 5 μm or more, more preferably 10 μm or more, and particularly preferably 15 μm or more.

[0089] When the non-aqueous electrolyte battery is a battery other than an all-solid-state battery, a non-aqueous electrolyte containing an electrolyte salt is used. The non-aqueous electrolyte generally uses a non-aqueous liquid electrolyte (hereinafter referred to as an "electrolyte"). In addition, as the electrolyte, an electrolyte in which an electrolyte salt such as a lithium salt is dissolved in an organic solvent is used. As the organic solvent, there is no particular limitation, and examples thereof include chain esters such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate; cyclic esters with high dielectric constants such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; mixed solvents of chain esters and cyclic esters, etc., and mixed solvents of chain esters as the main solvent and cyclic esters are particularly suitable.

[0090] As the electrolyte salt dissolved in the organic solvent when preparing the electrolyte solution, for example, LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiC4F9SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC n F 2n+1SO3 (n ≥ 2), LiN (RfSO2) (Rf'SO2), LiC (RfSO2) 3, LiN (Rf OSO2) 2 (wherein Rf, Rf' are fluoroalkyl groups), etc., or a mixture of two or more. The concentration of the electrolyte salt in the electrolyte is not particularly limited, but is preferably 0.3 mol / l or more, more preferably 0.4 mol / l or more, and preferably 1.7 mol / l or less, more preferably 1.5 mol / l or less.

[0091] In the nonaqueous electrolyte battery, in addition to the above-mentioned electrolytic solution, a gel-like electrolyte obtained by gelling the above-mentioned electrolytic solution with a gelling agent composed of a polymer or the like can be used as the nonaqueous electrolyte.

[0092] Figure 1 : is a longitudinal cross-sectional view schematically showing an example of a non-aqueous electrolyte battery manufactured by the manufacturing method of the present invention. Figure 1 The non-aqueous electrolyte battery 1 shown has a positive electrode 2, a negative electrode 3, and a separator (diaphragm or solid electrolyte layer) 4 between the positive electrode 2 and the negative electrode 3 enclosed in a battery container formed by an outer can 5, a sealing can 6, and a resin gasket 7 interposed therebetween. In addition, when the separator 4 is arranged between the positive electrode 2 and the negative electrode 3, a non-aqueous electrolyte containing an electrolyte salt is also enclosed in the battery container.

[0093] The sealing can 6 is fitted to the opening of the outer can 5 via the gasket 7 , and the opening end of the outer can 5 is tightened inwardly, whereby the gasket 7 abuts against the sealing can 6 , thereby sealing the opening of the outer can 5 and making the interior of the battery a sealed structure.

[0094] The negative electrode 3 includes a negative electrode active material layer composed of a lithium layer 31 and a lithium-aluminum alloy layer 32 , and a carbon layer 33 .

[0095] In the case of using a negative electrode having a lithium-aluminum alloy layer to manufacture a non-aqueous electrolyte battery, the negative electrode manufactured by the negative electrode manufacturing method of the present invention is used, and the positive electrode and the negative electrode are stacked with a separator or a solid electrolyte layer between them, or further wound to form an electrode body (stacked electrode body, wound electrode body, etc.), and the electrode body and a non-aqueous electrolyte containing an electrolyte salt such as an electrolyte solution (when a separator is used) are sealed in a battery container to manufacture a non-aqueous electrolyte battery.

[0096] On the other hand, when manufacturing a non-aqueous electrolyte battery, in the case of forming a lithium-aluminum alloy layer after the assembly of the battery, a negative electrode laminate formed by laminating a lithium layer and an alloy forming laminate is used to assemble the battery, and a negative electrode having a lithium-aluminum alloy layer is formed in the battery. More specifically, for example, the positive electrode and the negative electrode laminate are laminated across a separator, or further wound to form an electrode body (laminated electrode body, wound electrode body, etc.), and the electrode body and a non-aqueous electrolyte containing an electrolyte salt such as an electrolyte are sealed in a battery container to manufacture a non-aqueous electrolyte battery. At this time, since the negative electrode laminate is in contact with the non-aqueous electrolyte, a lithium-aluminum alloy layer is generated at the position of the aluminum foil to form a negative electrode (negative electrode active material layer) by the reaction between the lithium layer of the negative electrode laminate and the aluminum foil of the alloy forming laminate.

[0097] The form of the non-aqueous electrolyte battery is not particularly limited, and may be in various forms such as flat (including coin-shaped, button-shaped), laminated, cylindrical (cylindrical, square (square cylindrical)), etc. In addition, as the battery container (external body), a metal can (external can) and a cover (sealing can) having an opening may be used in combination, or a metal laminate film may be used.

[0098] Specifically, a flat or cylindrical battery can be produced by sealing the outer can and the sealing can by caulking them with a gasket or by welding them together. A laminated battery can be produced by overlapping two metal laminate films or by folding a metal laminate film and sealing them by bonding them together.

[0099] It should be noted that, in the case of a battery container body in the form of caulking and sealing, the raw material of the gasket sandwiched between the outer can and the sealing can can be PP, nylon, etc., and in the case of requiring particularly high heat resistance in relation to the battery use, fluororesins such as PFA, polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), PPS, PEEK, etc., heat-resistant resins having a melting point or thermal decomposition temperature of 200°C or above can also be used. In addition, when the battery is used for applications requiring heat resistance, the seal can also be sealed airtightly with glass.

[0100] Example

[0101] Hereinafter, the present invention will be described in detail based on examples. However, the following examples do not weaken the present invention.

[0102] (Example 1)

[0103] <Production of positive electrode>

[0104] A positive electrode mixture was prepared by mixing manganese dioxide as a positive electrode active material, carbon black as a conductive aid, and PTFE as a binder at a mass ratio of 90:5:5, and the positive electrode mixture was molded to obtain a positive electrode (positive electrode mixture molded body) with a diameter of 16 mm and a thickness of 1.8 mm.

[0105] <Production of Negative Electrode Laminated Body>

[0106] 100 parts by mass of acetylene black and 2 parts by mass of polyvinyl pyrrolidone were mixed in N-methyl-2-pyrrolidone to prepare a dispersion of acetylene black. The dispersion was applied to the surface of a long aluminum foil with a thickness of 9 μm using a coating machine and dried to prepare an alloy-forming laminate sheet having a carbon layer on one side of the aluminum foil. The unit area weight of the carbon layer was set to 1.0 mg / cm 2 .

[0107] Next, the above sheet was stacked on one side of a 1.2 mm thick lithium foil with the exposed surface of the aluminum foil on the lithium foil side, and this was punched into a circle with a diameter of 16 mm to obtain a negative electrode laminate consisting of a lithium layer, an aluminum layer, and a carbon layer.

[0108] <Preparation of non-aqueous electrolyte>

[0109] In a mixed solvent of propylene carbonate and 1,2-dimethoxyethane at a volume ratio of 1:1, LiClO 4 was dissolved at a concentration of 0.5 mol / l, and 2 mass % of 1,3-propane sultone was further added to prepare a non-aqueous electrolyte solution.

[0110] <Battery Assembly>

[0111] The positive electrode, negative electrode laminate and non-aqueous electrolyte were used, and a non-woven fabric made of polymethylpentene (thickness: 320 μm) was used as the separator. Figure 1 The structure shown is a coin-shaped non-aqueous electrolyte primary battery with a diameter of 20 mm and a height of 3.2 mm.

[0112] By bringing the negative electrode laminate into contact with a nonaqueous electrolyte in a battery container, a negative electrode active material layer having a lithium-aluminum alloy layer formed on the surface of the lithium layer is obtained, thereby obtaining a negative electrode further having a carbon layer on the above-mentioned lithium-aluminum alloy layer of the negative electrode active material layer.

[0113] (Example 2)

[0114] In addition to setting the unit area weight of the carbon layer constituting the alloy forming laminate sheet to 0.02 mg / cm 2 The same procedures as in Example 1 were followed to assemble a coin-shaped nonaqueous electrolyte primary battery.

[0115] (Example 3)

[0116] In addition to setting the unit area weight of the carbon layer constituting the alloy forming laminate sheet to 0.2 mg / cm 2 The same procedures as in Example 1 were followed to assemble a coin-shaped nonaqueous electrolyte primary battery.

[0117] (Example 4)

[0118] In addition to setting the unit area weight of the carbon layer constituting the alloy forming laminate sheet to 2.0 mg / cm 2 The same procedures as in Example 1 were followed to assemble a coin-shaped nonaqueous electrolyte primary battery.

[0119] (Comparative Example 1)

[0120] A 9 μm thick aluminum foil was pressed onto one side of a 1.2 mm thick lithium foil, and the foil was punched into a 16 mm diameter circle to obtain a laminate of lithium layer and aluminum layer. Next, the same acetylene black dispersion as that prepared in Example 1 was applied to the aluminum layer of the laminate and dried to prepare a negative electrode laminate having a carbon layer formed on the entire surface of the aluminum layer of the laminate. The unit area weight of the carbon layer was set to 1.0 mg / cm 2 .

[0121] Then, a coin-shaped nonaqueous electrolyte primary battery was assembled in the same manner as in Example 1 except that the negative electrode laminate was used.

[0122] (Comparative Example 2)

[0123] A coin-shaped nonaqueous electrolyte primary battery was assembled in the same manner as in Comparative Example 1 except that the surface of the stack of lithium layers and aluminum layers was not coated with the dispersion of acetylene black and the stack was used directly for battery assembly.

[0124] Each battery of Examples 1 to 4 and Comparative Examples 1 to 2 was discharged at room temperature to a charge equivalent to 120 mAh, and then kept in a thermostatic chamber at -40°C. After the temperature of the battery dropped, it was discharged at a current value of 10 mA, and the discharge voltage (CCV) of the battery was measured 10 ms after the start of discharge to evaluate the load characteristics at low temperature. The results are shown in Table 1.

[0125] [Table 1]

[0126]

[0127] The coin-shaped non-aqueous electrolyte primary batteries of Examples 1 to 4, which use an aluminum foil having a carbon layer pre-formed on the surface to form a lithium-aluminum alloy layer of the negative electrode, are easier to manufacture the negative electrode than the battery of Comparative Example 1 in which a dispersion of acetylene black is coated on a small area of ​​the aluminum foil in the negative electrode manufacturing process. In addition, as shown in Table 1, the load characteristics at low temperatures can be improved compared to the battery of Comparative Example 2 in which a carbon layer is not formed on the negative electrode.

[0128] Furthermore, by using an aluminum foil having a carbon layer formed on the surface in advance, the uniformity of the carbon layer can be improved compared to forming a carbon layer on a small area of ​​aluminum foil cut according to the negative electrode, and the deviation of the characteristics becomes smaller. Therefore, when the coin-shaped non-aqueous electrolyte primary battery of Example 1 using a negative electrode with a carbon layer having the same unit area weight is compared with the battery of Comparative Example 1, the battery of Example 1 can further improve the load characteristics at low temperature. Specifically, when 10 batteries of Comparative Example 1 are produced, the CCV value has a maximum deviation of about 0.07V relative to the central value, while in the battery of Example 1, the deviation of the CCV value is less than 0.02V.

[0129] (Example 5)

[0130] <Production of positive electrode>

[0131] The positive electrode mixture was prepared in the following steps. A conductive additive having a BET specific surface area of ​​800 m 2 After 2 parts by mass of Ketjen black (EC300J (trade name) manufactured by Lion Specialty Chemicals Co., Ltd.) with an average particle size of 35 μm as a positive electrode active material were dry-mixed for 5 minutes, water in an amount equivalent to 20% (mass ratio) of the entire solid content was added, and the mixture was further mixed for 5 minutes. Next, PTFE dispersion (Daikin Industries, Ltd. "D-1") was added in a ratio of 3.5 parts by mass of PTFE, and finally water was added until the overall solid content ratio became 74% by mass, and the mixture was further mixed for 5 minutes to obtain a positive electrode mixture.

[0132] Next, the positive electrode mixture was rolled into a sheet using a roller with a diameter of 250 mm and a temperature of 125 ± 5 ° C, and dried at a temperature of 105 ± 5 ° C until the remaining moisture was less than 2% by mass, thereby forming a preparatory sheet. Furthermore, the preparatory sheet was crushed into a powder with a particle size of about 0.5 mm or less using a pulverizer, and then rolled again using the roller, thereby forming a sheet with a thickness of 0.79 mm and a density of 2.89 g / cm 3 The content of manganese dioxide per unit area in the positive electrode mixture sheet is 0.216 g / cm 2 .

[0133] The obtained positive electrode mixture sheet was cut into positive electrode mixture sheet 1 with a width of 42.5 mm and a length of 67 mm (positive electrode mixture sheet arranged on the inner side when winding) and positive electrode mixture sheet 2 with a width of 42.5 mm and a length of 76 mm (positive electrode mixture sheet arranged on the inner side when winding).

[0134] The positive electrode current collector uses an expanded metal mesh made of stainless steel (SUS316). The expanded metal mesh is cut into pieces with a width of 39 mm and a length of 60 mm. A stainless steel strip with a thickness of 0.1 mm and a width of 3 mm is installed in the central part of the length direction by resistance welding as a positive electrode lead. Furthermore, carbon paste (manufactured by Nippon Graphite Co., Ltd.) is applied to the expanded metal mesh to a degree that does not damage the mesh, and then dried at a temperature of 105±5°C to form a positive electrode current collector. It should be noted that the amount of carbon paste applied is 5 mg / cm 2 .

[0135] Next, in a state where the above-mentioned positive electrode current collector is interposed between the positive electrode mixture sheet 1 and the positive electrode mixture sheet 2, only one end in the length direction is fixed to integrate each positive electrode mixture sheet with the positive electrode current collector. Specifically, one end in the length direction of the positive electrode mixture sheet 1 and the positive electrode mixture sheet 2 is aligned, and the end of the above-mentioned positive electrode current collector is arranged in a manner that does not extend from the above-mentioned end of the two positive electrode mixture sheets. In this state, the two positive electrode mixture sheets are pressed together at a position 5 mm away from the above-mentioned end, thereby integrating each positive electrode mixture sheet with the positive electrode current collector. Then, hot air drying is performed at 300±10℃ for 15 minutes, thereby obtaining a sheet-shaped positive electrode with a thickness of 1.6mm and a width of 42.5mm.

[0136] <Production of Negative Electrode Laminated Body>

[0137] The same method as in Example 1 was used except that the thickness of the aluminum foil was changed to 6 μm, and a carbon layer (weight per unit area: 1.0 mg / cm 2) alloy forming laminated sheet, cut a strip-shaped sheet 1 with a width of 40 mm and a length of 96 mm and a strip-shaped sheet 2 with a width of 40 mm and a length of 57 mm. Next, on a copper foil (negative electrode collector) with a width of 43 mm, a length of 173 mm and a thickness of 15 μm, a lithium foil 1 with a width of 42 mm, a length of 96 mm and a thickness of 0.29 mm and a lithium foil 2 with a width of 42 mm, a length of 57 mm and a thickness of 0.29 mm were placed at intervals of 9 mm in the length direction. Furthermore, the strip-shaped sheet 1 was placed on the lithium foil 1 and the strip-shaped sheet 2 was placed on the lithium foil 2 in a manner that the aluminum foil and the lithium foil were in contact, thereby forming a sheet-shaped negative electrode laminate with a collector. The ratio of the area of ​​the aluminum foil to the area of ​​the lithium foil was 95%, and the lithium foil and the aluminum foil were aligned and overlapped at both ends in the length direction and at the ends in the width direction that became the bottom side of the battery when inserted into the outer can. Furthermore, a negative electrode lead body made of nickel having a width of 3 mm, a length of 20 mm, and a thickness of 0.1 mm was previously crimped onto the lithium foil.

[0138] <Production of Electrode Body>

[0139] Two PE microporous films (porosity: 46%, air permeability: 200 sec / 100 mL, puncture strength: 380 g) with a width of 49 mm, a length of 180 mm, and a thickness of 16 μm were stacked and used as a separator.

[0140] The two overlapping PE microporous films are pasted on the copper foil between the two lithium foils of the sheet-like negative electrode stack, and then the portion to which the separator is pasted is clamped by a winding core (diameter: 2.8 mm) cut into two halves. After the negative electrode stack is rolled up together with the separator for about one week, the positive electrode is further placed and wound in such a way that the fixed end of the positive electrode mixture sheet becomes the winding core side, thereby obtaining a spiral electrode body.

[0141] <Battery Assembly>

[0142] An insulating plate made of PP with a thickness of 0.2 mm is inserted into the bottom of a bottomed cylindrical outer can made of nickel-plated stainless steel, and the above-mentioned electrode body is inserted thereon with the positive lead body facing upward, and the electrolyte is injected and sealed, thereby assembling a cylindrical non-aqueous electrolyte primary battery with an outer diameter of 17.0 mm and a total height of 50 mm. It should be noted that the electrolyte uses a non-aqueous solution in which LiCF3SO3 is dissolved at a concentration of 0.7 mol / L in a mixed solvent of ethylene carbonate, propylene carbonate and dimethoxyethane (volume ratio of 1:1:3). In addition, in the above-mentioned assembly process, a negative electrode active material layer having a lithium-aluminum alloy layer formed on the surface of the lithium layer (lithium foil) is obtained, and a negative electrode further having a carbon layer is formed on the above-mentioned lithium-aluminum alloy layer of the negative electrode active material layer.

[0143] <Preparatory discharge, aging>

[0144] The assembled battery was pre-discharged at a resistance of 1Ω for 30 seconds, stored at 70°C for 6 hours, and then pre-discharged twice for 1 minute at a constant resistance of 1Ω. The pre-discharged battery was aged at room temperature for 7 days, and the load characteristics at low temperature were evaluated under the conditions described below.

[0145] (Comparative Example 3)

[0146] A cylindrical nonaqueous electrolyte primary battery was produced in the same manner as in Example 5 except that a sheet-shaped negative electrode was formed by laminating only an aluminum foil having a thickness of 6 μm on a lithium foil instead of the alloy-forming laminate sheet.

[0147] The cylindrical non-aqueous electrolyte primary batteries of Example 5 and Comparative Example 3 were discharged at room temperature at a current value of 40 mA for 60 hours until the remaining capacity of the battery reached about 30% of the designed capacity. Then, the battery was kept in a thermostatic chamber at -30°C. After the temperature of the battery dropped, it was discharged at 100 mA, and the discharge voltage (CCV) of the battery was measured 10 ms after the start of discharge to evaluate the load characteristics at low temperature. The results are shown in Table 2.

[0148] [Table 2]

[0149]

[0150] In the cylindrical nonaqueous electrolyte primary battery, as in the above-mentioned coin-shaped nonaqueous electrolyte primary battery, the load characteristics at low temperatures can be improved.

[0151] The present invention can also be implemented in other ways than those described above without departing from the scope of its purport. The embodiments disclosed in this application are merely examples, and the present invention is not limited to these embodiments. The scope of the present invention is interpreted preferentially by the records of the attached claims compared to the description of the above-mentioned specification, and all changes within the scope equivalent to the claims are included in the claims.

[0152] Industrial Applicability

[0153] The nonaqueous electrolyte battery produced by the method of the present invention can be applied to various uses of conventionally known nonaqueous electrolyte primary batteries and nonaqueous electrolyte secondary batteries.

[0154] Description of Reference Numerals

[0155] 1: non-aqueous electrolyte battery, 2: positive electrode, 3: negative electrode, 31: lithium layer, 32: lithium-aluminum alloy layer, 33: carbon layer, 4: isolation layer, 5: outer can, 6: sealing can, 7 gasket.

Claims

1. A laminated sheet for alloy formation, which is an independent sheet consisting of an aluminum foil and a carbon layer formed on one side of the aluminum foil, The surface of the aluminum foil opposite to the carbon layer is brought into contact with the lithium layer to form a lithium-aluminum alloy layer on the surface of the lithium layer.

2. The alloy forming laminate sheet according to claim 1, wherein: The carbon layer contains at least one carbon material selected from the group consisting of graphite, carbon black, and fibrous carbon.

3. The alloy forming laminate sheet according to claim 1, wherein: The unit area weight of the carbon layer is 0.15 to 3 mg / cm 2 .

4. The alloy forming laminate sheet according to claim 1, wherein: The thickness of the aluminum foil is 1 to 20 μm.

5. A method for manufacturing a negative electrode for a non-aqueous electrolyte battery, wherein the negative electrode for a non-aqueous electrolyte battery comprises a negative electrode active material layer and a carbon layer, wherein the negative electrode active material layer comprises a lithium layer and a lithium-aluminum alloy layer formed on the surface of the lithium layer, and the carbon layer is formed on the surface of the negative electrode active material layer, characterized in that: The manufacturing method comprises: laminating the alloy forming laminate sheet and the lithium layer so that the surface of the aluminum foil of the alloy forming laminate sheet opposite to the carbon layer contacts the lithium layer; and and forming the negative electrode active material layer by reacting the lithium in the lithium layer with the aluminum in the aluminum foil.

6. A method for manufacturing a non-aqueous electrolyte battery, wherein the non-aqueous electrolyte battery comprises a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode, characterized in that: The negative electrode comprises a negative electrode active material layer and a carbon layer, wherein the negative electrode active material layer comprises a lithium layer and a lithium-aluminum alloy layer formed on the surface of the lithium layer, and the carbon layer is formed on the surface of the negative electrode active material layer. The negative electrode is formed by the method for producing a negative electrode for a non-aqueous electrolyte battery according to claim 5 .

Citation Information

Patent Citations

  • Current collector

    WO2012108212A1

  • Halide solid electrolyte material and battery using same

    WO2020070955A1

  • Halide solid electrolyte material and battery using same

    WO2020070958A1

  • Non-aqueous electrolyte battery and production method for same

    WO2020250816A1